OPERASI TANGKAP TANGAN (OTT) DI PUSAT DAN DAERAH UNTUK MERAIH WTP TERKAIT MASALAH PELANGGARAN HUKUM - Asyari, Fatimah (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2017)
The obyective of this research is to know the handle of the handcatch operation (OTT) not only in the central governent but also in the regional ones.The method of this is qualitative by library research and taking the news from  either magazine or regional , national daily news papers and other mass media .The results of the research are (1). The capture of the BPK auditor and staff are surprise;(2).The OTT distruction of the reputation of BPK;(3).This incident in this department is the first one.(4).The activity of will largely efect to the regional;(5).The result of OTT will bigger and bigger in the future,(6).The involved becomes more and more until to the regional;(7).Generally the heads of the Department from Political parties it is, therefore , they are not experts and controlled by the political party concerned. (8).The getting of the WTP in the regions have to be ditected ; The suggestions are (1).The OTT action has to be minimalizd by working honestly;(2).The OTT acion should be the last one                                                                                            for BPK;(3).The OTT action will not be happened in other institutions;(4). The OTT action by KPK KPK  will be the red notice.